Assessment fairness in freedom of learning in open and distance education - Nurhayati, Suci; Puryati, Puryati (REID (Research and Evaluation in Education), 2022)
This research aims to analyze or obtain a comprehensive overview of fairness in independent campus programs in open and distance education by looking at the conformity of the concept of assessment fairness themes in the practice of assessment on the program. This research was conducted using a qualitative research design, and the data obtained were analyzed descriptively. Data collection was carried out by conducting in-depth interviews with seven sources with competencies related to independent campus programs and their policies at the Universitas Terbuka as organizers of open and distance education systems, using interview guides and documentation studies. Data were transcribed and encoded according to their category. The results show that the conformity of the concept of assessment fairness in assessment practices on independent campus programs in open and distance education has largely been met. The theme of transparency, consistency, and justification, doing no harm to and constructive classroom environment, and avoiding score pollution is the most prominent in the fulfillment of indicators.